Impact Of Liquidity, Leverage And Size Of The Company On Profitability In Retail Trade Sub-Sector Companies Listed On The Indonesia Stock Exchange - Widia Astuty; Elly Susanti; Hery Pandapotan Silitonga (International Journal of Educational Research & Social Sciences, 2021)
The purpose of this study is to analyze the impact of liquidity, leverage and the size of the company on profitability. In this study liquidity is projected on Current Ratio (CR), Leverage is projected on Debt To Equity Ratio (DER), Company size is projected on Size and Profitability is projected on Return on Equity (ROE) This study was conducted on retail trade sub-sector companies during the period 2015-2020, sampling was conducted purposive sampling so that the sample in this study as many as 5 companies. The data is collected using documentation techniques, while data analysis uses classic assumption tests and hypothesis testing. From this study obtained the results that CR, DER and Size have a significant influence simultaneously on profitability. Cr partially has a positive and significant influence on ROE while DER and SIZE have a positive and insignificant influence on ROE.